Situation of Addictive Substance Use Among Nacrotics Drug Users in Health Service Region 3, 2009 – 2014 - Koranee, Rames; Aunchai, Chotika; Ditsawan, Anusorn; Pomyai, Siriporn; Vinissorn, Thippayaporn (Journal of Health Science of Thailand, 2017)
The wide-spread utilization of nacrotics drugs in Thailand has become a major national problem causing impact on economics and national security as well as the destruction of human security, leading to the deterioration of the potential of lives and the future of the country. To assess the extent and the severity of varieties of narcotic drug among drug users in the Public Health Region 3 of Thailand, the authors had studied drug specimens submitted to the Medical Sciences Center Region 3 by the police, health facilities, educational institutions, and others settings in the region including Kamphaeng Phet, Phichit, Nakhon Sawan, Uthai Thani, and Chainat provinces. Data were collected during the period from 2009-2014. It was found that there were altogether 13,564 specimens; and narcotic drugs were detected in 11,915 samples (87.84%). Majority of the drug users were in the age range of 21-30 years old (38.84%), followed by young people aged 20 and lower (26.03%). Most of them were employees (64.98%), followed by agriculturers (5.82%). The most common narcotic drugs were methamphetamine (99.17%), followed by cannabis (0.57%). Information from this study could be useful for drug control agencies to conduct surveillance and control of narcotic drug use in order to limit the spread of drugs in the Thai society.